2021
DOI: 10.3390/asi4040079
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic Location Intelligence System as Response to the COVID-19 Outbreak in Bosnia and Herzegovina

Abstract: The outbreak of COVID-19 is a public health emergency that caused disastrous results in many countries. The global aim is to stop transmission and prevent the spread of the disease. To achieve it, every country needs to scale up emergency response mechanisms, educate and actively communicate with the public, intensify infected case finding, contact tracing, monitoring, quarantine of contacts, and isolation of cases. Responding to an emergency requires efficient collaboration and a multi-skilled approach (medic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…As a technology, GIS provides a complete solution for preparing data, building platforms, creating models, and producing maps. In a number of recent studies, spatial solutions provided by GIS has been found to have much potential for preventing and controlling COVID-19, with the most significant aspects being enhanced prevention measurements and the evaluation of controls (Karabegovic et al, 2021;Sarwar et al, 2020).…”
Section: Role Of Location Intelligencementioning
confidence: 99%
“…As a technology, GIS provides a complete solution for preparing data, building platforms, creating models, and producing maps. In a number of recent studies, spatial solutions provided by GIS has been found to have much potential for preventing and controlling COVID-19, with the most significant aspects being enhanced prevention measurements and the evaluation of controls (Karabegovic et al, 2021;Sarwar et al, 2020).…”
Section: Role Of Location Intelligencementioning
confidence: 99%
“…Moreover, another article [8] published via this special issue explaining that responding to a COVID-19 situation necessitates effective coordination and a multi-skilled approach (information, medical, statistical, social, political, and other skills), making it difficult to establish a single interface for everyone. According to the authors, a geoportal has been designed as an epidemiological location-intelligence system that facilitates the sharing of such information across entities and cantons.…”
Section: Editorialmentioning
confidence: 99%